The DOOR to Antibiotic Stewardship: Refining Assessments of Interventions With Desirability of Outcome Ranking. (June 2022) - Smoke, Steven M.; Patel, Vishal V.; Leonida, Nicole I.
Background: Limited sample size and disparate outcome measures can hinder the ability of antimicrobial stewardship programs to assess the utility of their quality improvement interventions. Desirability of outcome ranking (DOOR) is a novel methodology that incorporates multiple outcomes into a single value to more comprehensively compare therapeutic strategies. The objective of this study was to apply DOOR to a single center antibiotic stewardship intervention. Methods: A pre- and post-interventional study was conducted evaluating the impact of prospective pharmacist review of rapid molecular diagnostic testing (RDT) of blood cultures on antibiotic optimization. Outcomes included the percentage of patients who were switched to appropriate therapy, the time to appropriate therapy, and the percentage of patients who had missed de-escalation opportunities. Results: A total of 19 and 29 patients were included in the final analysis. The percentage of patients reaching appropriate therapy was 84% (16/19) and 97% ([28/29], p = 0.16) in the pre-intervention and post-intervention groups respectively. Median time to appropriate therapy was 26 hours and 36 minutes (IQR 13:05-50:45) and 22:40 (IQR 3:42-48:23, p = 0.32), respectively. One missed de-escalation opportunity was identified in the post-intervention group (0% vs 3%, p = 1.00). DOOR analysis indicated that the probability of a better outcome for the post-intervention group than the pre-intervention group was 58% (95% CI 54-62). Conclusion: In this analysis, DOOR revealed a benefit that would not have been apparent with traditional outcomes assessments. Antimicrobial stewardship programs conducting quality improvement studies should consider incorporating DOOR into their methodology.